Phytochemical Properties, Antioxidant Activity and a- Amilase Inhibitory of Curcuma Caesia - Sri Kartinil, Sri Kartinil; Siti Juariah, Siti Juariah; Dini Mardhiyani, Dini Mardhiyani; Abu Bakar, Moh Fadzelly; Abu Bakar, Fazleen Izzani; Susi Endrini, Susi Endrini (semarak ilmu, 2023)
Diabetes mellitus (DM) is a metabolic disease characterized by hyperglycemia, which produces free radicals, particularly reactive oxygen species (ROS), through glucose auto-oxidation and glycosylation. Administration of antioxidants and poiyphenolic compound components can capture free radicals and reduce oxidative stress. Polyphenols are also able to reduce blood glucose levels by inhibiting the action of amylase enzymes as carbohydrate catabolism so that glucose absorption does not occur. One of the plants that contain polyphenols is Black Turmeric (Curcuma caesia). Some studies on the rhizomes of this plant include methanol extracts containing phenolics, Flavonoids, alkaloids, triterpenoids, saponins, and tannins. Dry powders and wet rhizome powders were studied to have antioxidant activity. Research on the inhibition of the enzyme alfa amylase is still lacking. This study aims to determine the content of chemical compounds using 70% ethanol solvent. The total phenolic and flavonoid assay with spectrophotometry, determine antioxidant activity using DPPH (2,2-dipheny1-1- picrylhydrazyl) at 490 nm and inhibition of cc-amylase enzyme using 3,5- dinitro salicylic acid (DNS) at 529 nm. The results showed that phenolic levels were 235 mgGAE/103gr, flavonoids were 61 mg CLE/100gr, Alkaloids 30 mg quinine /100gr and saponin 158 mg quillaja bark/100gr, dan tannin 535mg tannic acid/100gr. DPPH antioxidant activity obtained IC50 value of 299,18 pg/mLpig/m1 and a- amylase inhibitory 50,26 kg/mLpigimL. The research showed that 70% ethanol extract Curcuma caesia roxb contains phenolic, flavonoids, alkaloids, quinine, and saponins constituents and have been antioxidant activity and high a-amylase inhibitory